Gestational surrogacy: results of 10 years of experience in the Netherlands. Issue 6 (December 2018) - Peters, Henrike E.; Schats, Roel; Verhoeven, Marieke O.; Mijatovic, Velja; de Groot, Christianne J.M.; Sandberg, Joanna L.; Peeters, Immelie. P.; Lambalk, Cornelis B.
Abstract: Research question: What are the reproductive and obstetric outcomes of the gestational surrogacy treatment in the Netherlands? Design: This retrospective cohort study reports all data of gestational surrogacy treatment in the VU University Medical Centre over a period of 10 years. Data was collected from 60 intended parents and 63 gestational carriers, including reproductive and obstetric outcomes. Results: All intended mothers had a medical indication for gestational surrogacy and used autologous oocytes, and semen of the intended father. Ninety-three IVF cycles were initiated in 60 intended mothers, with subsequent 184 single embryo transfers in 63 gestational carriers. This resulted in 35 ongoing singleton pregnancies. At least one live birth was achieved for 55.0% of intended couples. Pregnancy was complicated in 20.6% by a hypertensive disorder. Labour was induced in 52.9%, and the Caesarean section rate was 8.8%. None of the pregnancies was complicated by preterm birth. Postpartum haemorrhage (>500 ml) occurred in 23.5%. Conclusions: This study shows the effective results of the non-commercial gestational surrogacy programme in the Netherlands, in a multidisciplinary team setting. An increased risk for adverse obstetric outcomes in surrogate mothers is noted for hypertensive disorders and post-partum haemorrhage compared with the incidence in non-surrogacy pregnancies.